2011
DOI: 10.2202/1446-9022.1213
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Platforms

Abstract: This article investigates the pricing decisions in two-sided markets when several platforms are needed simultaneously for the successful completion of a transaction. The results indicate that the anticommons problem generalizes to two-sided markets. On the other hand, the limit of an atomistic allocation of property rights is not monopoly pricing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The two Belgian financial newspapers De Tijd (in Dutch) and L'Echo (in French) represent complementary platforms. In fact, both papers connect Dutch-and French-speaking readers with companies that want to convey information (Van Cayseele and Reynaerts, 2011). So, to reach both Dutch-and French-speaking investors, companies need to buy advertisement space in both newspapers, which represent complementary inputs for the provision of corporate information.…”
Section: An Economic Viewpoint: Artificial Intelligence Platforms And...mentioning
confidence: 99%
“…The two Belgian financial newspapers De Tijd (in Dutch) and L'Echo (in French) represent complementary platforms. In fact, both papers connect Dutch-and French-speaking readers with companies that want to convey information (Van Cayseele and Reynaerts, 2011). So, to reach both Dutch-and French-speaking investors, companies need to buy advertisement space in both newspapers, which represent complementary inputs for the provision of corporate information.…”
Section: An Economic Viewpoint: Artificial Intelligence Platforms And...mentioning
confidence: 99%
“…Interestingly, Van Cayseele and Reynaerts (2011) were also able to test whether the results obtained by Dari-Mattiacci and Parisi (2006) indirectly apply to complementary platforms. They found that the bundle price (that is, the sum of the prices of all patents) set by independent complementary platforms does not approach the monopoly price as the number of platforms tends to infinity.…”
Section: Multi-sided Markets and Complementary Platformsmentioning
confidence: 99%
“…Changes in the level of inter-network compatibility positively affect the weak platform's marginal incentives to invest and negatively affect those of the dominant one. 28 In sum, two salient aspects of the compatibility-welfare puzzle follow. First, substitutes goods are "bad" for compatibility.…”
Section: Final Remarksmentioning
confidence: 99%